Induced Resistance of Shallot (Allium cepa L. var aggregatum) against Twisted Disease Using Ultraviolet-B Light - Ahmad, Yan Syahrial; Wibowo, Arif; Widiastuti, Ani (Universitas Gadjah Mada, 2023)
Ultraviolet-B (UV-B) light is known to induce plant resistance in suppressing disease infection. Its ability to induce plant resistance has been widely used as an inducer of plant resistance. This study aims to determine the ability of UV-B light in suppressing shallot twisted disease, potency of plant resistance induction through accumulation of peroxidase enzymes, salicylic acid, chlorophyl content and to observe shallot growth after treatment. This study applied UV-B light with a duration of 65 mW/m2 for 4 hours each day for 3, 5 and 7 days, for inoculated and non-inoculated plants. Fungicide (Benomyl) was used as a comparison for inoculated plants. The results showed that UV-B irradiation of 4 hours/day for 7 days was able to reduce the incidence of shallot twisted disease, but the incubation period among treatments was not significantly different. UV-B irradiation of 4 hours/day, for 7 days was able to increase salicylic acid content, and maintain the same chlorophyll content as the negative control, however the peroxidase enzyme content was not significantly different. Treatment of UV-B 4 hours/day for 7 days irradiation did not inhibit the growth and production of shallot plants.